The impact of halal certification and halal awareness on consumer intentions to purchase skincare products online - Putri, Yulianty Chi; Sjabadhyni, Bertina (Islamic perspective on Communication and Psychology, 2025)
Background: The growing awareness of halal products, particularly in the skincare industry, has prompted a need to understand the factors influencing Generation Z's purchasing intentions for halal skincare products through e-commerce platforms. Halal certification and halal awareness are critical factors in shaping consumer behavior. This study aims to examine the role of halal certification and halal awareness in influencing the purchasing intentions of Generation Z consumers for halal skincare products. Methods: This research employed a quantitative approach with a descriptive and cross-sectional design. Data was collected through surveys distributed to Generation Z consumers who had experience with halal skincare products. Structural Equation Modeling (SEM) was used to analyze the relationships between halal certification, halal awareness, and purchasing intentions. Findings: The results revealed that halal certification had a significant positive impact on consumers' intentions to purchase halal skincare products online, whereas halal awareness did not significantly predict purchasing intentions. This suggests that consumers' perceptions of halal certification are more influential than their awareness of halal products in driving their purchasing behavior. Conclusion: The study concludes that while halal certification plays a crucial role in influencing Generation Z's purchasing intentions, halal awareness alone does not significantly affect their decisions. Therefore, businesses in the halal skincare industry should focus on promoting halal certification to enhance consumer confidence and drive purchases. Novelty/Originality of this article: This article contributes to the understanding of consumer behavior in the context of halal skincare products, particularly by focusing on Generation Z and their online purchasing intentions. It provides new insights into the relative importance of halal certification over halal awareness in influencing purchasing decisions. Additionally, the study highlights the need for further research to explore the effects of religiosity and specific educational interventions on halal consumer behavior.